Crystallographic Studies of Enzymes (Volume II) - Kim, Kyeong Kyu; Kim, T. Doohun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue of Crystals, entitled "Crystallographic Studies of Enzymes (Volume II)", eleven research papers on key findings and methodologies of structure, function, and reaction mechanisms of enzymes are presented.